Entrepreneurship toolkit for adult educators and migrant support workers - Souleles, Nicos; Sampdanis, Marios; Savva, Stefania; Ferreira, Ana Margarida; Laghos, Andrew (My University, 2020)
This toolkit provides a collection of embedded-learning and design-based learning activities and resources. It is based on a pedagogical framework informed by the European Entrepreneurship Competence Framework (EntreComp) for entrepreneurship education and developed specifically by the Creation team. CREATION (Cultural and Arts Entrepreneurship in Adult Education) is a European Union-funded project under Erasmus+ that aims to explore the theoretical roots, pedagogical approaches and practical training in cultura entrepreneurship, specifically targeting underrepresented groups, i.e. women from marginalised backgrounds. The intention is for educators and migrant workers to use this toolkit to teach basic cultural entrepreneurial skills and competences to marginalised adult women. The toolkit is divided into three thematic units: Museums, Design and Arts and Crafts.
Keywords: Cultural entrepreneurship; Refugees; Migrants; Women